Cultural Resource Management in the Great Basin 1986-2016 - Fowler, Don D., 1936-; DeBunch, Patricia A.; Baldrica, Alice M. (Book collections on Project MUSE., 2019)
"Cultural Resource Management (CRM) refers to the discovery, evaluation, and preservation of culturally significant sites, focusing on but not limited to the archaeological and historical. CRM stems from the National Historic Preservation Act, passed in 1966. In 1986, archaeologists reviewed the practice of CRM in the Great Basin. They concluded that it mainly was a system of finding, flagging, and avoiding -- a means of keeping sites and artifacts safe. Success was measured by counting the number of sites recorded and acres surveyed"--Provided by publisher.